2004
DOI: 10.1128/jvi.78.14.7717-7726.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Carries a Cell-Derived Phospholipase A2 Required for Infectivity

Abstract: Human cytomegalovirus (HCMV) is known to carry host cell-derived proteins and mRNAs whose role in cell infection is not understood. We have identified a phospholipase A2 (PLA2) activity borne by HCMV by using an assay based on the hydrolysis of fluorescent phosphatidylcholine. This activity was found in all virus strains analyzed and in purified strains. It was calcium dependent and was sensitive to inhibitors of cytosolic PLA2 (cPLA2) but not to inhibitors of soluble PLA2 or calcium-independent PLA2. No other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In a recent report, Allal et al (45) have found that cPLA 2 ␣ is one of the several host-derived proteins carried by human cytomegalovirus. Although the function of these host cell-derived proteins is mostly unknown, cPLA 2 ␣ has been suggested to be required for proper infectivity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Allal et al (45) have found that cPLA 2 ␣ is one of the several host-derived proteins carried by human cytomegalovirus. Although the function of these host cell-derived proteins is mostly unknown, cPLA 2 ␣ has been suggested to be required for proper infectivity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a long time that c-PLA2 activity can be induced by HCMV infection (1), but more interestingly, a connection between infection and PPAR␥ activation was supported by a study demonstrating that HCMV particles carry a cell-derived PLA2 that is boarded during the assembly process, which plays a major role in infectivity of MRC5 fibroblasts (2). PLA2 activity is responsible for the production of arachidonic acid, a substrate for both Cox-2 and lipoxygenase activities, and we assume that it is a reason why c-PLA2-specific inhibitors dramatically impair virus production (2).…”
Section: Discussionmentioning
confidence: 99%
“…When calcium was not required, Ca 2+ /Mg 2+ free-PBS was used. Concentrations of inhibitors and their specifi city have already been documented ( 24,25 ). When GTP dependency was checked, the nonhydrolysable analog of GTP (GTP ␥ S) was added 10 min before monitoring phospholipase activity.…”
Section: Methodsmentioning
confidence: 99%
“…2C ). The concentration of inhibitors was 50 µM; i.e., above that used to inhibit the various PLA 2 in cells ( 24,25 ). The sum of the inhibitions triggered by pyrrolidine-1 and BEL in exosomes.…”
Section: Lipid-related Proteins In Exosomesmentioning
confidence: 99%